2015
DOI: 10.1039/c5ob01679g
|View full text |Cite
|
Sign up to set email alerts
|

Highly regioselective para-methylthiolation/bridging methylenation of arylamines promoted by NH4I

Abstract: Aryl methyl thioethers and methylene-bridged arylamines were synthesized via highly regioselective para-methylthiolation/bridging methylenation of arylamines using DMSO as the methylthio or methylene source in the presence of NH4I under metal-free conditions. For the substrates with both electron-donating and electron-withdrawing substituents, the reaction proceeded smoothly and gave moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 52 publications
4
13
0
Order By: Relevance
“…Our previous work confirmed that DMSO may produce methylthio radical in the presence of NH 4 I and the methylthiolation product maybe generated, 16 but no -SCH 3 substituted imidazoheterocycles were detected in the present reaction systems. The deuteriumlabeling experiment confirmed that the methylene group in product 2a completely originated from DMSO (eq 1).…”
Section: Scheme 4 Bridging Methylenation Of Imidazoheterocycles With supporting
confidence: 82%
See 2 more Smart Citations
“…Our previous work confirmed that DMSO may produce methylthio radical in the presence of NH 4 I and the methylthiolation product maybe generated, 16 but no -SCH 3 substituted imidazoheterocycles were detected in the present reaction systems. The deuteriumlabeling experiment confirmed that the methylene group in product 2a completely originated from DMSO (eq 1).…”
Section: Scheme 4 Bridging Methylenation Of Imidazoheterocycles With supporting
confidence: 82%
“…Our previous work confirmed that DMSO may produce methylthio radical in the presence of NH 4 I and the methylthiolation product maybe generated, 16 but no -SCH 3 substituted imidazoheterocycles were detected in the present reaction systems. 16,18,20 Acid-catalyzed addition of 2-phenylimidazo [1,2a]pyridine (1a) to CH 2 O generated an unstable cation A, 21 followed by elimination of H 2 O to form B. to the model reaction did not affect the yield evidently (eq 2).…”
Section: Scheme 4 Bridging Methylenation Of Imidazoheterocycles With supporting
confidence: 82%
See 1 more Smart Citation
“…Subsequently, Sun and co‐workers reported a highly regioselective para ‐methylthiolation/bridging methylenation of arylamines by using DMSO as the methylthio or methylene source (Scheme e) 37. In the presence of NH 4 I, various aryl methyl thioethers and methylene‐bridged arylamines were synthesized in moderate to good yields.…”
Section: As ‘S(o)xme’ Sourcesmentioning
confidence: 99%
“…By this strategy, a series of coumarin derivatives, a class of very important heterocyclic compounds in pharmaceuticals as well as in fluorescent materials, were synthesized via the addition of several radicals to aryl alkynoates, in which diselenides, Togni’s reagent (trifluoromethylation reagent), dialkyl H-phosphonates, sulfonylhydrazides, sulfinic acids, α-keto acids, ethyl bromo­difluoro­acetate, NIS, and 2,4-diones were employed as the radical sources. In continuation of our study on the covalent bond activation of inert solvents and their application in organic synthesis, in this work, we selected acetonitrile as the cyanomethyl source, through a peroxide promoted C–H bond activation and addition to the carbon–carbon triple bond of aryl alkynoates, followed by cyclization to synthesize 3-cyanomethylated coumarins.…”
mentioning
confidence: 99%